Energy consumption, economic growth and greenhouse gas emissions in the European Union countries - Lapinskienė, Giedrė; Peleckis, Kęstutis; Slavinskaitė, Neringa (Journal of Business Economics and Management, 2017)
This paper investigates the relationship between economic growth, greenhouse gas emissions and other factors based on the panel data of 22 countries of the EU in the period 1995–2014. The fixed effect panel model was used as a framework for the analysis. The novel contribution of this paper is that the factors of economic growth, energy consumption, energy taxes as well as R&D were tested in one expanded EKC model, including the data of three Baltic States. The regression coefficients referring to GDP, Energy consumption have a positive sign, while R&D and Energy taxes have a negative sign. The empirical analysis combines two steps of evaluation of panel models of different groups of countries. The results imply that the analysed factors (energy consumption, energy taxes as well as R&D) can be applied to adjust the EKC trend in the region and might be useful for the climate change policy adjustment.